Management of Pseudophakic Retinal Detachment - Aziz ur Rahman, Abdul Fattah, Asfandyar Asghar, Waseem Jafri (Pakistan Journal of Ophthalmology, 2007)
Objective: To evaluate the functional and anatomical outcome of retinal detachment surgery in pseudophakic eyes Material and Methods: Non comparative interventional case study was conducted at Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Malir Karachi from 1st January to December 2005. Study include 23 pseudophakic eyes of 23 patients with pseudophakic retinal detachment, who underwent three ports pars plana vitrectomy with silicone oil tamponade and endolaser. Postoperatively 3 months follow up was carried out. Results: 22 of 23 pseudophakic eyes (95.65%) achieved anatomical success. 20 pseudophakic eyes (86.95%) showed postoperative visual acuity improvement 1 or more lines ranged from 0.025-0.33 (1/60 – 6/18). Post operative complications include raised IOP in 14 eyes (60.86%), epiretinal membrane formation in 10 eyes (4.3%) and re-detachment in 01 eye (4.3%). Conclusion: Pseudophakic retinal detachment (RD) is always a complicated sort of detachment due to poor visualization of retinal breaks. Therefore scleral buckling (SB) alone is not sufficient to treat the RD. Three ports pars plana vitrectomy with silicone oil tamponade along with endolaser around the retinal breaks or 360o endolaser is an effective procedure to treat pseudophakic RD.